Аналіз технічних та соціальні перспектив розвитку систем запису та обробки інформації - Прокоф’єв, К. А. (ХНУРЕ, 2025)
In the modern world, the creation, recording, and processing of information is an integral part of various fields of activity, including science, the media industry, education, and business. Quality software plays a key role in ensuring the effective storage, organization, and analysis of data. This paper examines existing programs for recording and processing information, highlighting their features, technical and social problems, as well as the prospects for the development of this area.
Keywords: запис інформації; обробка інформації